2019
DOI: 10.1590/0102-311x00010719
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de adoçantes no Brasil: uma abordagem a partir de um inquérito domiciliar

Abstract: Resumo: O objetivo foi estimar a prevalência do uso de adoçantes pela população adulta brasileira e características dos usuários. Análise de dados da Pesquisa Nacional de Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM, 2014), um inquérito nacional de base populacional. O desfecho de interesse foi o uso autorreferido de adoçantes entre brasileiros com 20 anos ou mais. As variáveis analisadas foram sexo, idade em anos completos, região do Brasil, escolaridade em anos completos e classificaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
4
1
1
Order By: Relevance
“…The estimated prevalence of LNCS use in the current study is comparable to estimates reported by others (Zanini Rde et al 2011;Silva Monteiro et al 2018;Arrais et al 2019). Zanini Rde et al (2011) reported that 19% of adults (>20y) surveyed in Pelotas, the third most populous city in the southern state of Rio Grande do Sul, add sweeteners to their beverages, with prevalence increasing from 8.7% among the 20-29y subgroup to 32% among the 60 + y subgroup.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The estimated prevalence of LNCS use in the current study is comparable to estimates reported by others (Zanini Rde et al 2011;Silva Monteiro et al 2018;Arrais et al 2019). Zanini Rde et al (2011) reported that 19% of adults (>20y) surveyed in Pelotas, the third most populous city in the southern state of Rio Grande do Sul, add sweeteners to their beverages, with prevalence increasing from 8.7% among the 20-29y subgroup to 32% among the 60 + y subgroup.…”
Section: Discussionsupporting
confidence: 88%
“…The percent consumers from these studies are comparable to the percent consumers of tabletop sweeteners presented in Table 5 for adults 19-59y (10.9%) and 60 + y (26.5%). On the other hand, the prevalence of LNCS consumption in a study conducted by Geraldo and Pinto-e-Silva (2016) in 2016 among staff of two public universities in the state of São Paulo, Brazil was 54%, higher than the prevalence estimated in the current study and those estimated by Zanini Rde et al (2011), Arrais et al (2019), andSilva Monteiro et al (2018). Geraldo and Pinto-e-Silva (2016) attributed the higher estimated prevalence of LNCS consumers in their study as compared to those obtained by Zanini Rde et al (2011) to regional, income, and male to female ratio differences between the two studies.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In this study, ageing, the NCS use was more frequent among individuals who reported being on a diet and taking supplements; comparable results were observed in studies carried out in Brazil (20,42,43) and other countries (44,45) , which showed that dietary changes motivated by the desire to lose weight, a healthy lifestyle or a better health condition were associated with NCS use. In addition, the use of NCS was related to a higher intake of fruits and vegetables and selected micronutrients.…”
Section: Discussionsupporting
confidence: 87%